Second nature geography and regional income disparities in Colombia (2008)
In this paper, we derive and estimate a New Economic Geography model for the Colombian departments. We first derive an econometric specification relating wages to a distance weighted sum of the volumes of economic activities of the surrounding locations. Them, we test our econometric specification with data for Colombian departments in the period 1975-2000. The empirical results confirm the theoretical predictions of our model, showing that second nature geography factors (access to consumer markets) are a key variable in explaining the spatial distribution of wages in Colombia.